Women's Resistance Amidst Masculinity Through Body Politics - khoiron (MIMBAR : Jurnal Sosial dan Pembangunan, 2025)
In this article, the author describes how women's bodies are used to fight against the hegemonic masculine regime. Men's rejection of women has marginalized women's positions in politics, bureaucracy, including in the art of music. From here, this article aims to describe how women's skill in using their bodies amidst male power. Therefore, the author's argument is that in the midst of the ongoing patriarchal culture, through her body Inul articulates body politics as a marker of women's political practices. The purpose of this article is to reveal how women are able to resist through their bodies that have been disciplined by the state. In this research, the method used is a literature study related to the controversy of Inul Daratista's dance amidst the hegemony of men. Therefore, in this research, several findings were found, including: a) MUI Fatwa against pornography and pornoaction. b) Various rules on pornography c. The body as a political instrument. From here, Inul's agility and skill in political articulation through the body are used in carrying out her resistance.